PENGARUH KEMUDAHAN DAN KEAMANAN TERHADAP KEPUASAN KONSUMEN FINTECH - Chusnah, Chusnah; Indriana, Khairunnisa Tri (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
This research’s purpose is to know the effect of “Safety and Easiness Impact to Fintech’s Consumer Satisfaction” of Dana Application. This research had more than 35.000.000 population of DANA user, with sample of 96 respondents. The examination instrumental is by using validity and reliability test. Classical assumption test that used in this research is normality, multicorneallity, heteroscedasticity, and autocorrelation. Analytical method that used in this research is simple regretion, correlation, coefficient of determination and partial hypothesis testing, and t testing. Based on analytical data result and discussion, easiness is giving positive and significant impact to consumer satisfaction with thitung 8,699 < ttabel 1,661 with satisfaction level of 0,000 < 0,005, the correlation value is 0.668 which mean it have strong relation and coefficient of determination of 0,446 with percentage of easiness variable at 44,6% while the rest of value is effected by other factors. Partial safety gives positive and significant impact to consumer satisfaction with thitung 9,443 < ttabel 1,661 with significance level of 0,000 < 0,005, with correlation value at 0,698 which mean it have strong relation and coefficient of determination at 0,487 point with percentage of easiness variable at 48,7% while the rest of the value is effected by other factors.